Assessing the Determinants and Prospects for the Pace of Market Access by Countries Emerging from Crisis : Further Considerations. (Policy Papers; Policy Paper ;, 2005)
This paper essentially confirms the main findings of the paper previously discussed by the Board. It (i) discusses the external conditions and the domestic economic policy stance needed for a country to reaccess international Capital markets and (2) describes other considerations to reaccess markets, including a communications strategy and the design of debt instruments to regain market access.